2020
DOI: 10.1017/jfm.2020.681
|View full text |Cite
|
Sign up to set email alerts
|

On the spectral behaviour of the turbulence-driven power fluctuations of horizontal-axis turbines

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…The phase relationship between the three blades ensures that the effect of the profile is negated at this frequency in the combined rotor load measurements-however, the effect of the profile can be observed in rotor quantities at the third harmonic of the rotational speed. This agrees with the findings of Section 4.3 and the findings of [19,39]. Given the effect of the profile on generating the dominant amplitude within the BRBM structures, it was expected that discrepancies between the amplitudes measured at the differing depths (and hence differing positions within the profiled flow) would be observed-however, this was not the case, suggesting that a more drastic profile is required before such significant changes in the BRBM spectra occur.…”
Section: Power Spectral Densitysupporting
confidence: 87%
See 1 more Smart Citation
“…The phase relationship between the three blades ensures that the effect of the profile is negated at this frequency in the combined rotor load measurements-however, the effect of the profile can be observed in rotor quantities at the third harmonic of the rotational speed. This agrees with the findings of Section 4.3 and the findings of [19,39]. Given the effect of the profile on generating the dominant amplitude within the BRBM structures, it was expected that discrepancies between the amplitudes measured at the differing depths (and hence differing positions within the profiled flow) would be observed-however, this was not the case, suggesting that a more drastic profile is required before such significant changes in the BRBM spectra occur.…”
Section: Power Spectral Densitysupporting
confidence: 87%
“…There have been many laboratory studies into differing aspects of the three flow artefacts discussed above. There have been many articles focused on quantifying and modelling HATT power production under turbulent flow cases with a focus on spectral characterisation and modelling of loading and power production [6,14,15,[18][19][20][21][22][23][24][25][26]. Many laboratoryscale experiments detail the effects of upstream devices both in low turbulence and high turbulence scenarios with results presented in a phenomenological sense [6,14,15,17,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it appears that the mean power generated by the turbine is insensitive to the inflow timescales at low tip-speed ratios, with the power curves resulting from the family of flows at constant I σ matching considerably for stalled flow around the blades. This turbine behaviour is unexpected, as previous research in the topic 21 finds that the turbine low-pass behaviour is not a property of the operating conditions.…”
Section: Fig 16 Dependence Of Power Due To Torque and Angular Velocmentioning
confidence: 63%
“…Earlier studies with tidal turbines reported a slope of −5/3 from the spectrum of the power output signal (e.g. Deskos et al 2020) resulting from the ambient turbulence governing the power fluctuation. However, our power spectra in figure 18 suggest that low-frequency changes in the power output of turbines in a large tidal array could be strongly affected by the wake meandering, depending on the turbine spacing and array layout.…”
Section: Turbine Loading Unsteadinessmentioning
confidence: 99%